Pengaruh Komunikasi Terapeutik Terhadap Tingkat Kecemasan Pada Anak Usia Sekolah yang Mengalami Hospitalisasi di Zaal Anak Rsud Bima - Aniharyati Aniharyati; Ahmad Ahmad (Bima Nursing Journal, 2019)
Hospitalization is a threatening experience for children. Anxiety is the most common form of response in children who are hospitalized, especially in school-age children who are trying hard to be independent and produce, this is caused by changes in their routine habits due to hospitalization and they are limited in dealing with it. The use of therapeutic communication approaches is believed can overcome the problems of children and the occurrence of crisis. To that end, the study aims to determine the effect of the implementation of therapeutic communication on anxiety levels in school-age children who are hospitalized at Zaal Anak Bima Regional General Hospital. The research design used was one group pre-test post-test village design. Population was 15 respondents who were taken accidentally according to inclusion criteria. Data were obtained through interviews with parents and direct observation of respondents. Data collected was then analyzed using t-tests. (different test) analyzed using SPSS. From the results of the analysis test it was found that the result of P <0.006 less than 0.05 means that therapeutic communication is influential and effective in reducing anxiety levels of school-age children who are hospitalized significantly. With these results, it can be said that the use of approaches through therapeutic communication very appropriate in overcoming the problems of children that can bring anxiety, for it is expected that all health workers, especially pediatric nurses to always do therapeutic education in providing nursing care to children